PEMUSATAN KEPEMILIKAN MEDIA MASSA DI INDONESIA: TINJAUAN ASPEK HUKUM - Aulia, Muhammad Zulfa; Raffles, Raffles (Jurnal Hukum & Pembangunan, 2021)
Today, mass media tend to be exclusively possessed by certain business groups who generally have affiliation to authorities or political parties. This article disscusses the concentration of mass media ownership in the light of constitutional and competition law. The article argues that the privatisation of business and politics towards public information through mass media, which is inevitable, has to be minimized. This due to the fact that mass media is one of pillars to which the democracy of a nation relies on. Despite the ownership of mass media which is a part of expressions (by some elites) of the people to performs such duties as the one guaranteed by the Constitution, the restriction of its ownership has to be attempted, since the business field uses limited public space to conduct business and perform democracy attached in it. In terms of the ownership of mass media centralizes among certain business holders, people have only few alternatives of information despite various media people might choose.